Meeting special educational needs in primary classrooms inclusion and how to do it - Briggs, Sue 1953- (Routledge, 2016)
There are greater numbers of children with Special Educational Needs and Disabilities (SEND) now attending mainstream schools. This fully updated and revised edition of Meeting Special Educational Needs in Primary Classrooms is written by an experienced teacher, adviser and SEN consultant and explains the challenges that these children face. This is a practical book full of guidance for teachers and teaching assistants who support children with SEND in mainstream primary classrooms.